Screening for contaminant hotspots in the marine environment of Kuwait using ecotoxicological and chemical screening techniques. Issue 2 (30th November 2015) - Smith, A.J.; McGowan, T.; Devlin, M.J.; Massoud, M.S.; Al-Enezi, M.; Al-Zaidan, A.S.; Al-Sarawi, H.A.; Lyons, B.P.
Abstract: Kuwait is a country with low rainfall and highly concentrated industrial and domestic effluents entering its coastal waters. These can be both treated and untreated. In this study we sampled a series of coastal and open-sea sites and used a variety of analyses to identify those sites requiring the most attention. We used a high throughput GC–MS screen to look for over 1000 chemicals in the samples. Estrogen and androgen screens assessed the potential to disrupt endocrine activity. An oyster embryo development screen was used to assess biological effect potential. The chemical screen identified sites which had high numbers of identified industrial and domestic chemicals. The oyster screen showed that these sites had also caused high levels of developmental abnormalities with 100% of embryos affected at some sites. The yeast screen showed that estrogenic chemicals were present in outfalls at 2–3 ng/l E2 equivalent, and detectable even in some open water sites. Highlights: Eighteen Kuwait marine sites were assessed for chemical contamination and toxicology. Many chemicals were detected using a rapid GC–MS screen. Oyster embryo development effects were shown. Estrogenic effects were detectable into coastal waters. Chemical analysis and biological tests identified similar worst sites.